Globe artichoke cultivation in Argentina - Garcia, Stella Maris (2015)
Horticulture in Argentina is an intensive activity that covers a smaller area than other agricultural activities, but involves a greater return per hectare. Agriculture occupies around 30% of Argentina’s total area of approximately 270 million hectares. Whilst only 2% of this area involves horticultural practices, it represents up to 11% of the value of Argentinian agricultural products. The horticulture area has expanded to approximately 500,000 hectares, but varies from year to year since most crops are annuals. Garlic, sweet potato, onion, lettuce, potato, pepper, beans, tomato, carrot, and squash comprise 85% of the total horticultural production value (Table 1). Annually, around 10 million people are employed in horticulture, making it an activity of important social value. The fresh market absorbs 90% of the country’s production, in wholesale and retail markets. The remaining 10% goes to industry, and is mainly processed as canned, frozen or dehydrated products and, to a lesser extent, as pickled or ground products. In recent years, an increase in the consumption of vegetables has been evident globally because consumers have become more aware of the benefits to human health. However, the mean vegetable daily intake in Argentina is approximately 140 g/person, far short of the 400 g/person recommended by the World Health Organization (WHO, 2012).